HLA-Cw*03-restricted CD8+ T-cell responses targeting the HIV-1 gag major homology region drive virus immune escape and fitness constraints compensated for by intracodon variation. - Honeyborne, I; Codoñer, F; Leslie, A; Tudor-Williams, G; Luzzi, G; Ndung'u, T; Walker, B; Goulder, P; Prado, J (2010)
The potential importance of HLA-C-restricted CD8+ cytotoxic T lymphocytes (CTL) in HIV infection remains undetermined. We studied the dominant HLA-Cw*03-restricted CTL response to YVDRFFKTL(296-304) (YL9), within the conserved major homology region (MHR) of the Gag protein, in 80 HLA-Cw*03-positive individuals with chronic HIV infection to better define the efficacy of the YL9 HLA-C-restricted response. The HLA-Cw*03 allele is strongly associated with HIV sequence changes from Thr-303 to Val, Ile, or Ala at position 8 within the YL9 epitope (P=1.62×10(-10)). In vitro studies revealed that introduction of the changes T303I and T303A into the YL9 epitope both significantly reduced CTL recognition and substantially reduced the viral replicative capacity. However, subsequent selection of the Val-303 variant, via intracodon variation from Ile-303 (I303V) or Ala-303 (A303V), restored both viral fitness and CTL recognition, as supported by our in vivo data. These results illustrate that HLA-C-restricted CTL responses are capable of driving viral immune escape within Gag, but in contrast to what was previously described for HLA-B-restricted Gag escape mutants, the common Cw*03-Gag-303V variant selected resulted in no detectable benefit to the host.